Contribution of Inflammation and Hypoperfusion to White Matter Hyperintensities-Related Cognitive Impairment - Huang, Chao-Juan; Zhou, Xia; Yuan, Xin; Zhang, Wei; Li, Ming-Xu; You, Meng-Zhe; Zhu, Xiao-Qun; Sun, Zhong-Wu (Frontiers in Neurology, 2022)
White matter hyperintensities (WMHs) of presumed vascular origin are one of the most important neuroimaging markers of cerebral small vessel disease (CSVD), which are closely associated with cognitive impairment. The aim of this study was to elucidate WMHs pathogenesis from the perspective of inflammation and hypoperfusion mechanisms. A total of 65 WMHs patients and 65 healthy controls were enrolled in our study. Inflammatory markers measurements ( hypersensitive C-reactive protein (hsCRP) and lipoprotein-associated phospholipase A2 (Lp-PLA2)), cognitive evaluation, and arterial spin labeling (ASL) MRI scanning were performed in all subjects. Multivariate logistic regression analysis showed that Lp-PLA2 was an independent risk factor for WMHs. Cerebral blood flow (CBF) in the whole brain, gray matter (GM), white matter (WM), left orbital medial frontal gyrus (MFG.L(orbital part), left middle temporal gyrus (MTG.L) and right thalamus (Tha.R) in the patients were lower than those in the controls, and CBF in the left triangular inferior frontal gyrus (IFG.L(triangular part) were higher in the patients than in the controls. There was a significant correlation between Lp-PLA2 levels and CBF in the whole brain (R=-0.417, P<0.001) and GM (R=-0.278, P=0.025) but not in the WM in the patients. Moreover, CBF in the MFG.L (orbital part) and the Tha.R was respectively negatively associated with trail making test (TMT) and Stroop’s color word (SCWT), suggesting the higher CBF, the better executive function. While the CBF in the IFG.L (triangular part) was negatively correlated with attention scores in Cambridge Cognitive Examination–Chinese Version (CAMCOG-C) subitems (R=0.288, P=0.020). Our results reveal the vascular inflammation roles in WMHs, which may through the regulation of CBF in the whole brain and GM. Additionally, CBF changes in different brain regions may imply a potential role in modulation of cognitive function in different domains.